Resveratrol Attenuates High Glucose-Induced Osteoblast Dysfunction via AKT/GSK3β/FYN-Mediated NRF2 Activation - Xuan, Yue; Wang, Jie; Zhang, Xiaohui; Wang, Jie; Li, Jiahao; Liu, Qingbo; Lu, Guangping; Xiao, Mengjie; Gao, Ting; Guo, Yuanfang; Cao, Cong; Chen, Ou; et al. (Frontiers in Pharmacology, 2022)
Osteoblast dysfunction, induced by high glucose (HG), exerts a negative impact on bone homeostasis and contributes to the pathology of diabetic osteoporosis (DOP). One of the most widely recognized mechanisms for osteoblast dysfunction is oxidative stress. Resveratrol (RES) is a bioactive antioxidant compound to combat oxidative damage, however, its role in the protection of HG-induced osteoblast dysfunction has not been clarified. Therefore, our study aimed to explore potential regulatory mechanisms of RES for attenuating HG-induced osteoblast dysfunction. Here, our results showed that osteoblast dysfunction under HG condition was significantly ameliorated by RES via activation of nuclear factor erythroid 2-related factor (NRF2) to suppress oxidative stress. Furthermore, using Nrf2-shRNA and wortmannin, we identified that activation of NRF2 via RES was regulated by AKT/glycogen synthase kinase 3β (GSK3β)/FYN axis.